Kepadatan dan Keragaman Kecoa pada Kantin Sekolah di Kecamatan Gunung Talang, Kabupaten Solok, Sumatera Barat - Irfany, Ghina Salsabila; Hestiningsih, Retno; Yuliawati, Sri; Kusariana, Nissa (Jurnal Riset Kesehatan Masyarakat, 2024)
Background: As a dangerous insect, cockroach can contaminate the human food anywehere, including in the school canteens. The objective of this research was to describe the cockroach population density and diversity at the school canteens.Method: A research was conducted in Gunung Talang district, Solok regency, in November 2022. A saturated samples survey research method with cross sectional research design was used. The research population were 21 schools canteens in Gunung Talang district. Data were collected through observation. The cockroaches were collected using sticky traps which were operated for two nights. Identification of cockroaches was done using a microscope based on the cockroaches identification key. The cockroaches were counted based on its species and locations. The data were analyzed descriptively.Results: The number of cockroaches collected from 21 school canteens were 98. As many as 47.62% of the canteens could be categorized as clean from cockroach or very low cockroach population and 33.33% of them had low cockroach population. As many as 9.53% of the canteens had moderate, 4.76% high, and 4.76% very high levels of cockroach population. Six canteens had more than one species of cockroach. The cockroaches species found were Periplaneta australasiae, Periplaneta americana, Blatella germanica and Pycnoscelus surinamensis.Conclusion: The cockroach density at the school canteens in Gunung Talang district was varied. Six school canteens did not meet the health standard based on cockroach population density (>2). Six school canteens had the cockroach diversity more than one species.